Energy and macronutrition intake and body image associated with nutritional status of students of MAN 21 Jakarta - Bella Puspita; Debby Endayani Safitri; Anna Fitriani (Arsip Keilmuan Gizi (AKG), 2025)
Overweight and obesity is one the serious health problems whose prevalence continues to increase every year and the fifth largest risk factor for death in the world. Many factors cause overweight and obesity in adolescents, one of which is consumption behavior and sedentary behavior. The purpose of this study was to determine the relationship between energy intake and macronutrients, consumption of vegetable and fruit, sedentary lifestyle, and body image with the nutritional status of students in MAN 21 Jakarta which was held in May 2022. This research is an quantitative study with a cross-sectional study design. Samples of 88 students was selected using simple random sampling. Data were collected through direct interviews using a 2x24 hours food recall form and Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and records using a modified Adolescent Sedentary Activity Questionnaire (ASAQ) and Body Shape Questionnaire (BSQ-34). Data taken in the form of nutritional status based on IMT/U index, student characteristics (gender and age), energy and macronutrient intake, consumption of vegetables and fruits, sedentary lifestyle, and body image using pearson and spearman rank correlation statistical test. The result of statistical test showed there was a significant relationship between energy intake (p<0.05), protein (p<0.05), fat (p<0.05), carbohydrates (p<0.05), body image (p<0.05) and the nutritional status of students at MAN 21 Jakarta. However, there was no significant relationship between vegetable and fruit consumption (p>0.05) and sedentary lifestyle (p>0.05) with the nutritional status of MAN 21 Jakarta students.